Effectiveness of participant recruitment strategies for critical care trials: A systematic review and narrative synthesis. (August 2021) - Raven-Gregg, Timia; Wood, Fiona; Shepherd, Victoria
Background: Critical care trials are limited by problems with participant recruitment, and little is known about the most effective ways to enhance trial participation. Despite clinical research improving in the past decades within intensive care, participant recruitment remains a challenge. Not all eligible patients are identified, and opportunities for enrolment into clinical trials are often missed. Interventions to facilitate recruitment need to be identified to improve trial conduct in the critical care environment. Therefore, we aimed to establish the effectiveness of recruitment strategies in critical care trials in order to inform future research practice. Methods: Databases including MEDLINE, Embase, CINAHL and PsycINFO were searched for English language papers from inception to February 2020. The objectives were to: (1) establish the effectiveness of recruitment strategies and (2) recommend how effective recruitment strategies can inform research practice. Two reviewers independently assessed papers for inclusion and critically appraised the quality of the studies. Discrepancies were discussed within the research team. Relevant data were extracted and thematically coded into five overarching themes using a narrative synthesis approach. The review was prospectively registered on PROSPERO (CRD42019160519). Results: The search resulted in 2509 initially identified articles, with 15 that met the inclusion criteria. Articles reported a combination of quantitative, mixed methods and qualitative studies and a range of low-, moderate- and high-quality studies. Although, in-keeping with narrative synthesis approaches, none were excluded based on methodological quality. Five themes were identified relating to: patient eligibility identification, who provides information and seeks consent, resource limitations, research culture or environment and the consent model used. The relative success of recruitment strategies was dependent upon the experience and availability of the staff involved in the approach, trial design, the application of the strategy to the specific intensive care environment, the acceptability of the recruitment and consent models used, and the efficiency of the recruitment procedures. Opportunities for consent were missed in a proportion of eligible patients in most studies, suggesting that clinicians may avoid recruiting more complex patients or in more complex situations and that further development of strategies is needed. Conclusion: More effective recruitment strategies are required to enhance recruitment and the representativeness of the patient sample obtained in critical care trials, in order to expand the evidence base for treatments in this field. Greater focus is needed on assessing the performance of different recruitment strategies within different types of studies and critical care research environments. Future research should explore key stakeholders' experiences of, and attitudes towards, recruitment and establish the most important and feasible modifiable barriers to recruitment.